Semantic Processing in Bilingual Aphasia: Evidence of Language Dependency - Calabria, Marco; Grunden, Nicholas; Serra, Mariona; García-Sánchez, Carmen; Costa, Albert (Frontiers in Human Neuroscience, 2019)
Individuals with aphasia frequently show lexical retrieval deficits due to increased interference of semantically related competitors, a phenomenon that can be observed in tasks such as naming pictures grouped by semantic category. These deficits are explained in terms of impaired semantic control, a set of abilities that are to some extent dependent upon executive control (EC). However, the extent to which semantic control abilities can be affected in a second and non-dominant language has not been extensively explored. Additionally, findings in healthy individuals are inconclusive regarding the degree to which semantic processing is shared between languages. In this study, we explored the effect of brain damage on semantic processing by comparing the performance of bilingual individuals with aphasia on tasks involving semantic control during word production and comprehension. Furthermore, we explored whether semantic deficits are related to domain-general (EC) deficits. First, we investigated the naming performance of Catalan-Spanish bilinguals with fluent aphasia and age-matched healthy controls on a semantically blocked cyclic naming task in each of their two languages. This task measured semantic interference in terms of the difference in naming latencies between pictures grouped by the same semantic category or different categories. Second, we explored whether lexical deficits extend to comprehension by testing participants in a word-picture matching task during a mixed language condition. Third, we used a conflict monitoring task to explore the presence of EC deficits in patients. We found two main results. First, in both language tasks, bilingual patients’ performances were more affected than those of healthy controls when they performed the task in their non-dominant language. Second, there was a significant correlation between the speed of processing on the EC task and the magnitude of the semantic interference effect exclusively in the non-dominant language. Taken together, these results suggest that lexical retrieval may be selectively impaired in bilinguals within those conditions where semantic competition is higher and this could be explained by an excessive amount of language inhibition. Moreover, lexico-semantic impairments seem to be at least somewhat related to conflict monitoring deficits, suggesting a certain degree of overlap between EC and semantic control.